Investigating students' approval of a geometrical approach to differential equations and their solutions - Habre, Samer (2003)
The advancement of computer graphics in the past decade has contributed to an enormous change in the way mathematics is taught at the college level. Although Calculus has been the main benefactor of this advancement, the topic of ordinary differential equations has undergone fundamental changes in its curriculum in favour of the visual and numerical aspects of the course. This paper investigates students' acceptance of solving a differential equation geometrically. The setting is an introductory course on ordinary differential equations offered to engineering students, in which a reformed approach was adopted. Data were gathered from exams, and interviews were conducted with six students who volunteered to take part in the study. Results show that students initially showed reluctance to accept this geometric approach, but many of them eventually accepted it, appreciated its usefulness, and wished that other math courses be offered in a similar way.